2017
DOI: 10.1186/s12889-017-4822-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors for Giardia and Cryptosporidium infections among children of northwest Mexico: a cross-sectional study

Abstract: Background G. intestinalis and Cryptosporidium spp. are responsible for gastrointestinal infections worldwide. Contaminated food, feces, drinking water and predictors such as poverty, cultural and behavioral aspects have been involved in their transmission. Published studies about these infections are limited in Mexico. Cananea, Sonora is located in northwest Mexico and is one of the regions with the lowest marginalization index in the Sonora state. However, its rate of gastrointestinal infections increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
3
11
0
2
Order By: Relevance
“…Two studies performed in Ethiopia reported that the prevalence was 7.3% and 4.6% among school children, respectively [ 23 , 24 ]. Quihui-Cota et al reported a high prevalence of 27% among children in Mexico [ 25 ]. The heterogeneity of the previously documented prevalence might to some extent be due to the socioeconomic level of the study site, the immune status of the targeted groups, and the sensitivity of the examining techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies performed in Ethiopia reported that the prevalence was 7.3% and 4.6% among school children, respectively [ 23 , 24 ]. Quihui-Cota et al reported a high prevalence of 27% among children in Mexico [ 25 ]. The heterogeneity of the previously documented prevalence might to some extent be due to the socioeconomic level of the study site, the immune status of the targeted groups, and the sensitivity of the examining techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not observe any association between “supplied with piped water” and Cryptosporidium infection. Previous studies revealed that tap water was a risk factor for Cryptosporidium infection in other regions [ 25 , 30 ]. In our study, supplied drinking water covered most of the households.…”
Section: Discussionmentioning
confidence: 99%
“…Meksika'da yapılan bir araştırmada, çocuklarda %23 oranında G. intestinalis infeksiyonu görüldüğü bildirilmiştir (9) . Schmidlin ve ark.…”
Section: Discussionunclassified
“…Entamoeba histolytica and Giardia lamblia are two protozoa that produce enteric infections with the common symptom of dysentery and acute diarrhea, which out constitute a serious public health problem in tropical regions around the globe, and are considered endemic in several countries of the African, American, and Asian continents (Marie and Petri 2014;Saidin et al 2019). Annually, each protozoan causes 50 and 280 million of cases respectively, and 100,000 deaths, being mainly affecting children younger than 10 years old (Rojas et al 2016;Quihui-Cota et al 2017;Ibañez-Cervantes et al 2018). The treatment of these kinds of infections is based on the use of synthetic antiprotozoal agents such as metronidazole, nitazoxanide, and tinidazole; however, these drugs have several adverse effects, as well as possible risks of carcinogenesis and mutagenesis with the use of metronidazole (Hayat et al 2016).…”
Section: Introductionmentioning
confidence: 99%